2004
DOI: 10.1029/2003jc002146
|View full text |Cite
|
Sign up to set email alerts
|

Hydrology and circulation in the Strait of Hormuz and the Gulf of Oman—Results from the GOGP99 Experiment: 2. Gulf of Oman

Abstract: [1] Hydrological, ADCP, and drifting buoy data obtained during the GOGP99 Experiment in October and early November 1999 are analyzed to describe the Persian Gulf Water (PGW) core and the regional circulation in the Gulf of Oman. The warm and salty PGW core flows out of the Strait of Hormuz heading southeastward unto (25°20 0 N, 57°E), approximately. From there, it cascades down the continental slope, veers southwestward, and joins the Omani coast near (24°50 0 N, 56°50 0 E) to form a slope current. This PGW cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 23 publications
9
62
2
Order By: Relevance
“…In some previous literatures (e.g. Senjyu et al, 1998;Bower et al, 2000;Pous et al, 2004) the mean depth of the outflow spreading in the Oman Sea has been found to be at about 250-400 m. The results of this simulation are more or less consistent with the measurements of Senjyu et al (1998) (Fig. 18), which have been made during January 1994, and the measurements of the Pous et al (2004), during October and early November 1999.…”
Section: The Outflow Spreading Pathwaysupporting
confidence: 82%
See 1 more Smart Citation
“…In some previous literatures (e.g. Senjyu et al, 1998;Bower et al, 2000;Pous et al, 2004) the mean depth of the outflow spreading in the Oman Sea has been found to be at about 250-400 m. The results of this simulation are more or less consistent with the measurements of Senjyu et al (1998) (Fig. 18), which have been made during January 1994, and the measurements of the Pous et al (2004), during October and early November 1999.…”
Section: The Outflow Spreading Pathwaysupporting
confidence: 82%
“…The Mediterranean outflow after passing Cape St. Vincent becomes hydro-dynamically unstable and lenses of saline water shed from the core and carry the outflow water characteristics into the Atlantic Ocean. Pous et al (2004) revealed short-term variability (about two weeks) of the Persian Gulf Outflow (PGO) by direct measurements using surface-drift buoys, hydrological and ADCP data. They attributed this variability to different mechanisms such as advection of the outflow, meander growth and eddy detachment from the outflow as it spreads into the Oman Sea, and diffusion of thermohaline properties of the outflow into the adjacent water masses.…”
Section: Ezam Et Al: Numerical Simulations Of Spreading Of the Pementioning
confidence: 99%
“…This speed should also be recorded regularly on the continental slope near Ra's al Hamra. Baroclinic instability has been mentioned by Pous et al (2004) to explain fragment detachment from the outflow in fall 1999 (during the GOGP1999 experiment).…”
Section: Recurrence Of Pgw Lensesmentioning
confidence: 99%
“…The PGW outflow was usually presented as a southeastward flow along the coast of Oman (see Premchand et al, 1986). Indeed, in October-November 1999, during the fall intermonsoon, the GOGP99 1 experiment at sea sampled the PGW outflow and identified it as a coastal flow, extending to the southern coast of Oman (see Pous et al, 2004). During other seasons, the path of the PGW in the Gulf of Oman is less regular, as shown by observations and by numerical modeling; also, PGW can exit in the form of short pulses (see Banse, 1997;Senjyu et al, 1998;Bower et al, 2000;Prasad et al, 2001;Thoppil and Hogan, 2009;Wang et al, 2012;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The outflow of the Persian Gulf, after entering the Sea of Oman near the break of the continental shelves, starts to sink towards the deeper part and mix with the surrounding waters as it reaches a buoyancy equilibrium depth of 100 -250 m. The thermohaline properties decrease in these areas due to strong mixing of the Persian Gulf outflow into the Oman Sea by the wind variability, bottom friction, breaking of the internal waves, until a depth of neutral buoyancy, about 220 meters [3] [4].…”
Section: Introductionmentioning
confidence: 99%